PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA INDONESIA (TKI) DARI PERBUDAKAN MODEREN DI TINJAU DARI UNDANG-UNDANG NOMOR 39 TAHUN 1999 TENTANG HAK ASASI MANUSIA (HAM) - Londar, Yohana; Murary, Weron; Syauta, Novalin M. (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: the purpose of this research is to determine the legal protection of Indonesian Migrant Workers (TKI) from Modern Slavery reviewed from Law Number 39 of 1999 concerning Human Rights (HAM) and to examine in more depth the factors that cause modern slavery to Indonesian Migrant Workers (TKI). In accordance with the objectives of the research above, it is hoped that this research can enrich the study and appreciation and benefits in providing legal protection for TKI from modern slavery and become input for the government and law enforcement so that they can be better in responding to modern slavery experienced by Indonesian Migrant Workers TKI. The research used is normative juridical research, where this research uses various approaches whose data sources use primary, secondary and tertiary legal material research, because this research was conducted at the Sorong Regency Regional Library, by collecting data to be used in this research in the form of a legislative approach and literature study. The analysis used in this study is a qualitative analysis approach which is carried out by tracing the legal materials that have been processed, such as laws and regulations and literature reviews which are then written descriptively and obtaining results by making conclusions that will be used in this study. The results of the study obtained by the author, in the form of Legal Protection for Indonesian Migrant Workers from modern slavery which is an effort by the government to provide proper protection for every citizen. By guaranteeing safety, security and welfare. So that there needs to be legal protection for Indonesian Migrant Workers so that they are free from discrimination and modern slavery. Cases that are often experienced by Indonesian Migrant Workers are cases of discrimination or modern slavery because Indonesian Migrant Workers are considered weak people who have no power whatsoever while under the auspices of their employers. Therefore, many Indonesian migrant workers are made into modern slaves who are forced to work or forced labor, their basic rights are not respected, they are made into sex slaves, traded (human trafficking), job opportunity fraud (illegal Indonesian migrant workers), weak law enforcement, lack of education and so on. These factors have resulted in modern slavery and have violated the provisions of government regulations and several articles in Law Number 39 of 1999 concerning Human Rights, which explains that human rights must be respected, honored, protected and upheld because they are a gift from God Almighty which is inherent and cannot be separated by anyone.Keywords: Indonesian migrant workers, Protection, From Slavery, Review of Law No. 39 of 1999.